Model Penguatan Institusional dalam Pemberdayaan Desa untuk Mewujudkan Nilai Publik di Kabupaten Banyuasin - Putra, M. Defri Adi Shah; Lionardo, Andries; Widodo, Slamet; Chendra, Rudy; Nasution, Chairika (PERSPEKTIF, 2026)
This study aims to analyze institutional dynamics in village empowerment and to formulate an institutional strengthening model based on public value in Banyuasin Regency. A qualitative approach with a case study design was employed to explore interactions among actors, values and norms, and institutional practices in village empowerment. Data were collected through in-depth interviews, observations, and document analysis involving key stakeholders at the village and local government levels. The findings indicate that village empowerment remains dominated by administrative orientation, with limitations in human resource capacity, low community participation, and weak internalization of public values. At the same time, opportunities for institutional strengthening emerge from resource availability, local potential, and multi-actor collaboration. This study proposes an institutional strengthening model that integrates structure, values, actors, and participatory processes to generate public value in the form of improved welfare, service quality, and public trust.